Editorial [Hot Topic: Alzheimer's Disease: Highlights from Research on Hormones, Growth Factors and Signaling Pathways (Debomoy K. Lahiri)] - Lahiri, Debomoy K. (Current Alzheimer Research, 2007)
Current Alzheimer Research enters the fourth year of successful publication with a great sense of fulfilling our mission. During the last year, five issues of its third volume have been completed and published on time. The third volume featured a total of 65 articles in addition to Editorials.These articles, comprising primary research articles and review papers, were written and peer-reviewed by experts in neuroscience and Alzheimer's disease (AD). Current Alzheimer Research remains an international journal as exemplified by contributions from researchers belonging to 19 countries: Australia, Austria, Belgium, Canada, China, France, Germany, India, Israel, Italy, Japan, Netherlands, Singapore, Spain, Sri Lanka, Taiwan, UAE, UK and the USA. Diversity of the experimental models discussed in the last volume, which ranged from cell culture-based to animal and human studies is also worth noting. Success of the journal is reflected in its acceptance for listing in PubMed/MEDLINE and other databases. The journal is currently accessible via online (http://www.bentham.org/car/) and abstracts of each article are freely available on the journal's website The focus of Current Alzheimer Research continues to be reporting mechanistic, drug-related and translational-based advances in Alzheimer's disease and related disorders. A wide range of topics in AD research, including amyloid biogenesis, brain imaging, immunotherapy, genetics, oxidative stress and tauopathy have been discussed by world renowned experts in the area, and several unique and controversial topics have been presented to encourage novel directions. In addition, the journal continues to publish results from clinical drug trials, including adequately-justified, evidencebased negative data. Covering the entire AD field is not an easy task, nor should it be our goal. For example, during the last single year alone, AD has captured over 3,800 citations on PubMED/MEDLINE search. Thus, the necessity of timely dissemination of this knowledge is of great importance. Although Current Alzheimer Research covers a small fraction of primary research, our review articles present a comprehensive overview of selected interesting topics, which makes an important contribution and provide a great resource to the AD field. In the current fourth volume, with at least 5 different issues, Current Alzheimer Research gears up to present a wide range of themes in the forms of critical review articles and original research reports, which are expected to address the neurobiology of AD, analyze potential drug targets, and elucidate novel therapeutic strategies. The journal plans to cover research topics in current molecular, genetic, and in vivo models. Like previous years, the 4th volume will occasionally bring special issues written by experts on different “Hot Topics” of AD. Indeed, the next issue of the journal will be a special ‘Hot Topic’ issue entitled “Exploring the Links between Obesity and Alzheimer Research” (Guest Editor: Dr. Suzana Petanceska). Issue 1 of the 4th volume contains 8 articles, which address both the most interesting and relevant topics in the field of AD and neurodegenerative disorders and the potential utility of several valid targets for the therapy of AD. The present issue is focused on understanding signaling pathways, the role of different hormones and growth factors and the relevance of each in therapeutic strategies. However, the converging connection of these various factors to the amyloid pathway has not been overlooked in most instances. Several lines of evidence suggest that G protein-coupled receptors (GPCRs) play an important role in cellular signaling. Indeed, manipulation of transmembrane signaling by GPCRs is one of the most important therapeutic targets although, it has not been fully exploited in AD and other neurodegenerative diseases. Maudsley and colleagues (page 3-19) present a timely review on the complexity of G proteincoupled receptor signaling in neuronal tissue and its implications for novel therapeutics. The authors note that, with better understanding of the complexity of GPCR signaling, the rational design of ligands possessing increased specific efficacy and attenuated side effects should become the norm for drug development using this important and ubiquitous target. In the context of signaling, Aghdam and Barger discuss (page 21-31) the potential for therapeutic use of lithium in neuroprotective strategies and further elaborate both the hopes and caveats of this strategy.....